Weight-bearing Imaging in Adolescent Idiopathic Scoliosis - Chiyanika, Chileka; Chu, Winnie Chiu Wing (Seminars in Musculoskeletal Radiology, 2019)
This article reviews the weight-bearing imaging methods in the diagnosis and monitoring of patients with adolescent idiopathic scoliosis (AIS), a three-dimensional (3D) deformity of the spine with unknown etiology. The apical vertebrae in AIS rotate away from the midline in a complex 3D pattern that formerly could only be appreciated by computed tomography (CT). Despite its superb anatomical delineation, CT is not ideal due to high radiation and scanning in either the supine or prone position; hence the full effect of gravity on the spinal curvature cannot be assessed. The introduction of low-dose stereoradiography with the capacity of 3D reconstruction has recently opened up a new era of assessment of the scoliotic spine in the upright position at multiple time points during the preoperative and postoperative period. The handheld 3D ultrasound imaging system also provides a radiation-free alternative for close monitoring for disease progression and treatment outcomes for AIS. Upright magnetic resonance imaging is radiation free and superb for the assessment of spinal cord and intervertebral disks; however, its utilization in scoliosis is limited by high cost and limited availability.
Keywords: scoliosis; low-dose stereoradiography; three-dimensional ultrasound; magnetic resonance imaging; computed tomography